Unbalanced Associations between Physical, Psychological, and Social Domains of the Leicester Cough Questionnaire: Network and Mediation Analyses - Jieun Kang; Jiyeon Kang; Sung Jun Chung; Hyung Koo Kang; Sung-Soon Lee; Yun-Jeong Jeong; Ji-Yong Moon; Deog Kyeom Kim; Jin Woo Kim; Seung Hun Jang; Jae-Woo Kwon; Byung-Jae Lee; et al. (Tuberculosis and Respiratory Diseases)
Background The Leicester Cough Questionnaire (LCQ) is a validated instrument for evaluating cough-related impairments within three domains: physical, psychological, and social. This study investigated how the physical, psychological, and social domains of chronic cough are interrelated using the LCQ. Methods Adult patients with chronic cough from 16 respiratory centers who completed the LCQ and underwent diagnostic workup were retrospectively reviewed. Spearman's rank correlation was used to examine the correlations among LCQ items across the physical, psychological, and social domains. Causal mediation analysis was performed to partition the total effect between domains into direct and indirect effects mediated by the third domain. The mediation analysis findings were subsequently validated in an independent cohort. Results Network analysis of LCQ items identified distinct patterns for each domain. Items in the physical domain showed weaker correlations both within and between domains compared to the psychological and social domains. In contrast, items in the psychological and social domains exhibited strong interrelationships. Mediation analysis demonstrated that direct effects from one domain to another differed among the three domains. The overall estimated effects of the physical domain on the social and psychological domains were largely mediated by the psychological (76.1%) and social domains (67.1%), respectively. Conversely, the mediating effect of the physical domain on the psychological and social domains was minimal, accounting for only 12.8% and 18.0%, respectively. Conclusion Given the strong correlations and impact of the psychological and social domains, it is recommended that a thorough evaluation including psychosocial factors be incorporated into the management of chronic cough.